Distribusi Peran Gender Pada Komunitas Amarima Hatuhaha Pulau Haruku, Maluku Tengah: Analisis Sosiologi Gender, Kekuasaan dan Kearifan Lokal di Pasar Mardika - Sarmalina Rieuwpassa; Hermien Soselisa; Christwyn R. Alfons; Johanis Talaperuw (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
Economic activities concentrated in Ambon City’s Mardika Market reveal a shift toward women playing an increasingly dominant role in the trade sector and the management of household finances. However, this shift does not automatically eliminate the role of men or the traditional values that have long underpinned the community’s social life. This study aims to analyze the distribution of gender roles within the Amarima Hatuhaha community on Haruku Island, Central Maluku, known as the “community of five sister villages” (Pelau, Kailolo, Rohomoni, Kabau, and Hulaliu). This community upholds the value of “orang basudara” (siblings) as the foundation of its social, economic, and traditional life. The study employs a qualitative approach using field observation and in-depth interviews with merchants and workers from the Hatuhaha community who are active at Mardika Market in Ambon City. The findings indicate that gender-based division of labor remains distinct, with men predominantly working in physically demanding sectors such as port laborers and motorcycle taxi drivers, while women dominate the trade sector. Women bear a double workload because they combine domestic and economic roles, yet they exercise significant control over the family’s finances. Customary norms are adaptive and non-restrictive; rather, they serve as a moral guide rooted in social solidarity. Gender relations in the Hatuhaha community are complementary and reflect the functional equality characteristic of the indigenous communities of Maluku